Tensor based machine learning frameworks for intrusion detection in the physical and network layers of cyber-physical systems - Maranhão, João Paulo Abreu (2021)
Tese (Doutorado em Engenharia Elétrica)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, Brasília, 2021.